2016
DOI: 10.1016/j.soildyn.2015.12.010
|View full text |Cite
|
Sign up to set email alerts
|

InterPACIFIC project: Comparison of invasive and non-invasive methods for seismic site characterization. Part I: Intra-comparison of surface wave methods

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(85 citation statements)
references
References 76 publications
7
77
0
1
Order By: Relevance
“…Moreover, sharp narrow spectral peaks may indicate the presence of electromagnetic disturbances or machinery generated noise (see also the SESAME guidelines, SESAME Team 2004). Figure 13 shows an analysis of power spectral density of the three sites investigated within the framework of the InterPacific project (Garofalo et al 2016a, b), compared to the NHNM, NLNM and theoretical self-noise of the sensor used in the passive surveys. One can see that around 3 Hz the Cadarache site has a power spectral density 4 orders of magnitude lower in comparison with the Mirandola site.…”
Section: Signal Quality Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, sharp narrow spectral peaks may indicate the presence of electromagnetic disturbances or machinery generated noise (see also the SESAME guidelines, SESAME Team 2004). Figure 13 shows an analysis of power spectral density of the three sites investigated within the framework of the InterPacific project (Garofalo et al 2016a, b), compared to the NHNM, NLNM and theoretical self-noise of the sensor used in the passive surveys. One can see that around 3 Hz the Cadarache site has a power spectral density 4 orders of magnitude lower in comparison with the Mirandola site.…”
Section: Signal Quality Controlmentioning
confidence: 99%
“…Feedback from InterPacific project Although no international consensus have yet been reached on the best way to estimate uncertainties for active surface wave analysis, the feedback from several international blind analysis projects (among them the InterPacific one, see Garofalo et al 2016a) shows that, within the reliable wavelength band, interanalyst uncertainties, estimated in terms of Coefficient of Variarion (COV), on the average phase velocity range from 5 to 10% depending on the sites (Fig. 27).…”
Section: Active Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, some studies have shown that this value is a good proxy of the V S30 (Martin and Diehl 2004;Albarello and Gargani 2010). For some sites where the dispersion curves were not strictly available at 40 m, we slightly extrapolated (or interpolated) dispersion curves to get the standard deviation at 40 m. The third option was to apply a 'minimum' fixed coefficient of variation based on the InterPacific project feedback (Garofalo et al 2016b) for the variability between the various analysts on the 'best' V S estimates. This minimum coefficient of variation was set at 10% when the R0 dispersion curve was available at k = 40 m, and was set at 20% when it was not available (this was often the case when only the MASW experiments were usable).…”
Section: Inversion and Derivation Of Velocity Profilesmentioning
confidence: 99%
“…Even if the capabilities of these methods have been debated for a long time, they provide good estimates when implemented with care, as demonstrated within the InterPacific project (Garofalo et al 2016a, b;Foti et al 2017). In particular, Garofalo et al (2016b) outlined that V S30 can be equally well estimated using 'noninvasive' approaches (e.g., surface-wave-based methods) and 'invasive' approaches (e.g., cross-holes, down-holes). However, Garofalo et al (2016a) also showed that noninvasive methods are less accurate for locating a given lithological interface, low velocity layers or bedrock depth.…”
Section: Introductionmentioning
confidence: 99%